FAKTOR-FAKTOR PENENTU PENILAIAN KEMBALI ASET TETAP UNTUK MENINGKATKAN ARUS KAS DAN POSISI PASAR - Yusuf, Dhandy; Satria, Indra; Sudarmaji, Eka (Universitas Trilogi, 2023)
This study discusses the implementation of fixed asset revaluation by taking case studies on manufacturing companies listed on the IDX in 2019-2021. Fixed asset revaluation is an action that may be required to describe the actual value of a company's assets accurately. This study aimed to determine the significance of leverage, decrease in operating cash flow, market book ratio, firm size, and intensity of fixed assets on revalued fixed assets. Statistical methods used in this study are descriptive statistics, overall fit model, fit test, Nagel Kerke (R-Square), and logistic regression. Samples were taken using a purposive sampling technique. The final sample is 193 manufacturing companies listed on IDX in 2019-2021. The results of this study indicated that company size and market book ratios significantly affect fixed asset revaluation. Leverage decreased operating cash flow and fixed asset intensity had no significant effect on the revaluation of fixed assets.Keywords: Cash flow, Company size, Fixed asset intensity, Fixed asset revaluation, Leverage, Market book ratio